An Analysis of Australia’s Foreign Policy through its Domestic Factors to Combat Child Sex Tourism in Project Childhood - Nathania, Christina; K, Megahnanda Alidyan (ARISTO, 2023)
2010 was the year Australia initiated and signed Project Childhood, a grant and partnership to protect children from sexual exploitation due to travel and tourism. Four countries in the Greater Mekong Subregion, Thailand, Cambodia, Laos, and Vietnam, are in a sub-region where child sex tourism occurs a lot. The phenomenon of transnational borders will involve sending country as the country of traveling child sex offenders, and receiving country for victims coordinates to make serious law enforcement regarding this issue. In formulating foreign policy, domestic factors are one way of looking at why Australia provides funding, assistance, and initiate international cooperation to combat child sex tourism in GMS. Through this research, the authors will explain the domestic factors that influence Australia in initiating Project Childhood as its foreign policy, using domestic determinants as the level of analysis. Then, it will be divided into 3 sub-determinants, they are; highly stable, demonstrating an Australian responsibility for TCSO originating in the country. This is related to one of the demographic components that cause migration problems. Moderately stable, in relation to the domestic reforms that are actively being carried out in the context of enforcing the extraterritoriality. The last, unstable, the factor of public opinion which also has played an important role so that the government gives attention to this phenomenon